Enhancement of polar phases in PVDF by forming PVDF/SiC nanowire composite - Huang, Jie-Fang; Han, Song-Jia; Chen, Hui-Jiuan; Liu, Gui-Shi; Li, Gong-Tan; Wang, Yu-Cheng; Wang, Zi-Xin; Yang, Bo-Ru; Luo, Zhenhua; Shieh, Han-Ping D. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
Different contents of silicon carbide (SiC) nanowires were mixed with Poly(vinylidene fluoride) (PVDF) to facilitate the polar phase crystallization. It was shown that the annealing temperature and SiC content affected on the phase and crystalline structures of PVDF/SiC samples. Furthermore, the addition of SiC nanowire enhanced the transformation of non-polar α phase to polar phases and increased the relative fraction of β phase in PVDF. Due to the nucleating agent mechanism of SiC nanowires, the ion-dipole interaction between the negatively charged surface of SiC nanowires and the positive CH2 groups in PVDF facilitated the formation of polar phases in PVDF.
Keywords: Decision support systems; content; Poly(vinylidene fluoride); silicon carbide nanowires; polar phase; annealing temperature